A Passive FPAA-Based RF Scatter Meteor Detector. (4th January 2016) - Popowicz, A.; Malcher, A.; Bernacki, K.; Fietkiewicz, K.
Abstract: In the article, we present a hardware meteor detector. The detection principle is based on the electromagnetic wave reflection from the ionized meteor trail in the atmosphere. The detector uses the ANADIGM field programmable analog array (FPAA), which is an attractive alternative for typically used detecting equipment—a PC computer with dedicated software. We implement an analog signal path using most of available FPAA resources to obtain precise audio signal detection. Our new detector was verified in collaboration with the Polish Fireball Network, the organization which monitors meteor activity in Poland. When compared with currently used signal processing PC software employing real radio meteor scatter signals, our low-cost detector proved to be more precise and reliable. Due to its cost and efficiency superiority over the current solution, the presented module is going to be implemented in the planned distributed detectors system.